2013
DOI: 10.1123/ijsnem.23.5.431
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Season-Long Vitamin D Supplementation on Collegiate Swimmers and Divers

Abstract: The purpose of this 6-month randomized, placebo-controlled trial was to determine the effect of season-long (September–March) vitamin D supplementation on changes in vitamin D status, which is measured as 25(OH) D, body composition, inflammation, and frequency of illness and injury. Forty-five male and female athletes were randomized to 4,000 IU vitamin D (n = 23) or placebo (n = 22). Bone turnover markers (NTx and BS AP), 25(OH)D, and inflammatory cytokines (TNF-alpha, IL-6, and ILl-β) were measured at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 31 publications
13
80
0
1
Order By: Relevance
“…For example, 400% more vitamin D and its photoproducts were synthesized in vacuoles containing 7-dehydrocholesterol (in ethanol) placed in noon sunlight at the base camp of Everest (5350 m, 28 °N) than in vacuoles pleased near sea-level (169 m, 27.2 °N)) (Holick et al, 2007). Another possibility is that college-age athletes tend to have better overall status (Lewis, Redzic, & Thomas, 2013;Storlie et al, 2011) than other athletic populations because they spend more time outdoors wearing less clothing. In the current study, better status was most likely due to sun exposure during leisure-time as NCAA-regulated training occurred either late afternoon (after 3 p.m.) or indoors, and was also not due to vitamin D supplementation or tanning bed use.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, 400% more vitamin D and its photoproducts were synthesized in vacuoles containing 7-dehydrocholesterol (in ethanol) placed in noon sunlight at the base camp of Everest (5350 m, 28 °N) than in vacuoles pleased near sea-level (169 m, 27.2 °N)) (Holick et al, 2007). Another possibility is that college-age athletes tend to have better overall status (Lewis, Redzic, & Thomas, 2013;Storlie et al, 2011) than other athletic populations because they spend more time outdoors wearing less clothing. In the current study, better status was most likely due to sun exposure during leisure-time as NCAA-regulated training occurred either late afternoon (after 3 p.m.) or indoors, and was also not due to vitamin D supplementation or tanning bed use.…”
Section: Discussionmentioning
confidence: 98%
“…Many factors impact an athlete's ability to maintain vitamin D status (Larson-Meyer & Willis, 2010) including training latitude, time spent training at close to solar noon, tanning bed use (Halliday et al, 2011;Lewis et al, 2013), skin pigmentation (Pollock, Dijkstra, Chakraverty, & Hamilton, 2012), sunscreen/sunblock use (Matsuoka, Ide, Wortsman, MacLaughlin, & Holick, 1987) and genetics (Fu et al, 2009). The current study also sought to determine whether body size and/or adiposity are also predictors of vitamin D status in athletes as it is in the general population (Arunabh et al, 2003;Drincic et al, 2012;Looker, 2005;Wortsman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have highlighted the causal link between low bone mineral density and the risk of stress fractures in athletes (Myburgh et al, 1990). Given these risks, adequate vitamin D levels are recommended to prevent injury in aquatic sports (Lewis et al, 2013). Care should be taken especially during fall and winter.…”
Section: Injury Preventionmentioning
confidence: 99%
“…In this study, vitamin D status was found to be below optimal values in a significant proportion of these athletes (Lovell, 2008). However, in a study investigating vitamin D status and supplementation in collegiate swimmers and divers training indoors, researchers observed a low prevalence of vitamin D insufficiency (25-hydroxy vitamin D < 32 ng/ml), and an absence of vitamin D deficiency (25-hydroxy vitamin D < 20 ng/ml; Lewis et al, 2013). There is a history of ultraviolet light therapy to ensure adequate vitamin D status for athletes.…”
Section: Vitamin Dmentioning
confidence: 97%